PENGARUH MEDIA SOSIAL TERHADAP PENGGUNAAN BAHASA INDONESIA DI KALANGAN GENERASI MUDA - Ocha Andini Fadilla; Naifah Nazla Husni; Tri Lande; Khairina Firantia Azha; Elsa Mulina Br. Napitupulu; Cela Talita Sianturi; Siti Apriyanti Majid (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The development of digital technology and social media has had a major impact on the use of the Indonesian language, especially among the younger generation. This study aims to analyze the influence of social media on the proper and correct use of Indonesian in daily communication. The research method used is qualitative research with a descriptive approach through literature studies and observations of language use on social media platforms such as Instagram, TikTok, and WhatsApp. Data collection techniques were carried out by reviewing scientific articles, journals, and examples of language use on social media. The results show that social media has positive impacts, such as increasing language creativity and facilitating communication. However, it also has negative impacts, including excessive use of slang, mixing Indonesian with foreign languages, and decreasing adherence to proper Indonesian language rules. Therefore, public awareness, especially among the younger generation, is needed to maintain the proper and correct use of Indonesian without eliminating the role of social media as a modern communication tool.